TEACHING CONTENT OF TECHNOLOGY IN POLISH PRIMARY SCHOOL - Grzegorzewska, Maria Katarzyna; Noga, Henryk; Migo, Piotr Pawel; Małodobry, Zbigniew (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
In view of the reform that is currently taking place in Poland, as well as changes in the content of the education curriculum, the authors of this study present contents of two selected curricula for primary schools technology in polish school. The study of research is content of curricula created by publishing house (WSiP) and Nowa Era. The school’s task is to prepare pupils for adult life, and therefore, bring the ability to create by themself a friendly environment. In each school there are such subjects, to which students participate more willingly than others - this situation can be used to reflect what affects their state of affairs. Comparing teachers opinions about the curriculum developed by Nowa Era and WSiP, it should be stated that the curriculum developed by the WSiP publishing house according to the opinion of the surveyed teachers has an advantage over the analogous program Nowa Era in the following areas: transparency, clarity, exhaustion topic, availability for the student.